Association between health care provider factors and the number of prenatal visits in Peruvian Hospital users: Asociación entre los factores del proveedor de salud y el número de atenciones prenatales en las usuarias de un Hospital Peruano - Diez Quevedo, Karina Elizabeth (2020)
Introducción: Maternal and child health care is a priority for health services, it is essential that all pregnant women comply with the necessary amount of prenatal care for proper supervision of pregnancy and the detection of possible warning signs or complications in a timely manner. Objective: To identify the association between the health provider factors and the number of prenatal care in the users of the Carlos Lanfranco La Hoz hospital attended in 2019. Methods: quantitative, relational and non-experimental design study. 342 pregnant users attended from January to December 2019, who were selected through a systematic probability sampling. For the statistical analysis, a descriptive statistic was used through the distribution of absolute and relative frequencies and an inferential statistic through the use of Poisson regression. Results: The age from 18 to 35 years (74%) predominated, the degree of secondary instruction (62.9%), the cohabiting marital status (71.1%) and the comprehensive health insurance (92.7%). The factors associated with the number of prenatal care were, as a scientific technical factor, receiving guidance on the results of analysis in prenatal care ”(p = 0.000; expB = 1.2 95% CI 1.10–1.39), and the doctor or obstetrician if recommended medications in their prenatal consultation (p = 0.003; expB = 1.2 95% CI 1.05-1.27); As a human factor, the doctor or obstetrician calls her by name during the prenatal visit (p = 0.000; expB = 1.5 95% CI 1.19–1.77). Conclusion: There is an association between the health provider factors and the number of prenatal care in the users of the Carlos Lanfranco La Hoz Hospital attended in 2019.